2008
DOI: 10.2136/sssaj2007.0345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Plant‐Available Potassium for No‐Till, Rainfed Soybean

Abstract: Temporal and spatial availability of K can influence soybean [Glycine max (L.) Merr.] productivity. This study quantified the impact of initial soil K concentrations, soil‐water content, and soybean K uptake on soil K pools (water‐extractable solution‐phase K [Ksol], 1 mol L−1 NH4OAc‐extractable K, referred to as exchangeable K (Kexch), and 5‐min sodium tetraphenylboron [NaTPB] extractable K [KTPB]) and compared predictions of plant K availability using the NaTPB vs. NH4OAc tests. Soil and soybean samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…Th e decline observed only in the soil surface is likely related to crop removal as these fi elds had <2% slope and nutrient loss by runoff is unlikely. Th ese data agree with other studies that indicate crop nutrient uptake occurs mostly on the surface layer of the soil (Fernández et al, 2008Farmaha et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…Th e decline observed only in the soil surface is likely related to crop removal as these fi elds had <2% slope and nutrient loss by runoff is unlikely. Th ese data agree with other studies that indicate crop nutrient uptake occurs mostly on the surface layer of the soil (Fernández et al, 2008Farmaha et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…In no-till studies with a broad range of K levels (160-400 mg kg −1 ), K concentrations at the 0 to 5 cm layer were 1.5 to 2 times the values observed in the 5-to 10-cm layer and 2 to 2.5 times the values in the 10-to 20-cm layer (Buah et al 2000;Hargrove 1985). Recently, Fernández et al (2008) documented a 5:2:1 ratio for these same layers in a field with longterm no-tillage and broadcast K management. In the eastern corn belt of the United States, vertical stratification of K in soil is a particular concern for soybean as the crop is rarely irrigated.…”
mentioning
confidence: 96%
“…In contrast, Ritchie et al (1994) found soybean accumulated only 50% of its total requirement by R4 at 70 days after emergence with 100% of uptake delayed until the very end of reproductive development (R7, 110 days after emergence). Furthermore, a typical soybean crop requires 73% more K in harvested grain when compared to maize (Fernández et al 2008 and references cited therein). However, existing recommendations do not account for crop differences in K demand (Purdue Crop Diagnostic Training and Research Center 2006); the advent of high fertilizer and crop prices has renewed interest in evaluating the need for crop-specificity in K recommendations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This advantage can increase accuracy in predicting plant K uptake, especially when plants obtain considerable amounts of K from nonexchangeable forms. On the other hand, some researchers reported that NaTPB has no advantage compared to the traditional methods for assessment of plant available K (Schindler et al, 2002;Fernandez et al, 2008). The effectiveness of solute used for assessment of available soil K seems largely dependent on the nonexchangeable K extracting power and extraction period of the method that different researchers employed.…”
Section: Introductionmentioning
confidence: 99%